Star Wars. Blast off! (New York : DK, 2010)
Describes the main characters which inhabit the Star Wars galaxy.
"Lucas Books."--P. [4] of cover.
Accelerated Reader AR
Keywords: Star Wars films -- Juvenile literature; Star Wars films -- Characters -- Juvenile literature; Star Wars fiction; Science fiction; Movie novels